ROLE OF DAMAGED HERITAGE RAPID ASSESSMENT IN POST-DISASTER RECOVERY PROGRAM - Punto Wijayanto (International Journal on Livable Space, 2016)
ABSTRACTIndonesia is a country located in the ring of fire. Various kinds of disasters threats parts of Indonesia, including its rich cultural and natural heritage assets. Since the 2004, Tsunami in Aceh, the government gives serious attention to disaster. In 2007, it stipulated the Law 24/2007 on Disaster Management. It's so unfortunate that cultural heritage is not yet part of main concern during disaster programs. In addition, there are only few experiences in the world about how to deal with the condition of heritage affected by disaster.      Heritage organizations in Indonesia aim to raise awareness about disaster risks on cultural heritage. They develop system of damage assessment to cultural heritage or Damage Heritage Rapid Assessment (DHRA) at the time of emergencies. Damage assessment was introduced in Yogyakarta, experienced a lot of damage caused by the massive earthquake in 2006. DHRA has been used in Padang (2009), Yogyakarta (2010), Jakarta (2013) and Manado (2014). This paper aims to explain what DHRA is and how DHRA can contribute to post-disaster rehabilitation and reconstruction of heritage district.Keywords: Damage assessment, disaster, heritage